From matter to essence. Sourcing raw materials for the votive artefacts of the megalithic communities in Ribeira da Seda (North Alentejo, Portugal): a preliminary approach. - Andrade, Marco António (2020)
This paper presents some preliminary readings about the procurement of raw materials for the production of votive artefacts by the megalithic communities in the area of Ribeira da Seda (North Alentejo, Portugal). A macroscopic analysis of the artefacts collected in megalithic monuments in the study area (pottery, flaked stone artefacts, polished stone artefacts, votive plaques, adornment elements, metallic artefacts, ground stone artefacts) allowed to evidence a relative diversity of the used materials – most of which, in percentage terms, corresponds to locally or regionally available raw materials, in the Ossa-Morena Meta-Volcanic Zone, reflecting the optimized maintenance of abiotic resources. Extraregional raw materials, such as flint, have statistically lower values when comparing only the types of raw material, indenpendently of the artefacts category and number; however, if we compare the number of artefacts per se, we note a marked weight of exogenous materials (for flaked stone artefacts, for instance, nearly 2/3 are produced on flint). This shows a constant procurement of this raw material, which is also associated with the presence of exotic materials (such as amber and ivory), framing the area of Ribeira da Seda in the wide interaction diagrams of the megalithic communities of the 4th and 3rd millennia BCE in Southwestern Iberia.